Abnormalities of the nocturnal blood pressure profile: significance, diagnostic possibilities, and therapeutic approaches - Zh. D. Kobalava; E. A. Troitskaya (Российский кардиологический журнал)
Impaired 24-hour blood pressure (BP) profile is receiving increasing attention due to improved detection capabilities, increased incidence, and confirmed associations with cardiovascular risk. However, there are gaps or conflicting data in knowledge about nocturnal hypertension (HTN) and non-dipping. The review focuses on current problems associated with elevated nocturnal BP with an emphasis on diagnostic capabilities, prognostic significance of changes and treatment options.